2019
DOI: 10.1093/mnras/stz074
|View full text |Cite
|
Sign up to set email alerts
|

New evidence for Dicke’s superradiance in the 6.7 GHz methanol spectral line in the interstellar medium

Abstract: We present new evidence for superradiance in the methanol 6.7 GHz spectral line for three different star-forming regions: S255IR-NIRS3, G24.329+0.144, and Cepheus A. Our analysis shows that some of the flux-density flares exhibiting fast rise times and asymmetric light curves reported in these sources can naturally be explained within the context of superradiance. When a threshold for the inverted population column density is exceeded in a maser-hosting region, the radiation mode switches from one regulated by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…The possibility of a rapid increase in the maser pumping efficiency that is accompanied by only small changes in continuum emission should be explored akin to the arguments put forward in Sobolev et al (1997). Another possibility might be superradiance as described by Rajabi et al (2019) pertaining to the flaring methanol masers associated with S255IR-NIRS3. It is not clear what best describes the conditions of the maser environment nor this rapid variation presented here.…”
Section: An Accretion Event?mentioning
confidence: 99%
“…The possibility of a rapid increase in the maser pumping efficiency that is accompanied by only small changes in continuum emission should be explored akin to the arguments put forward in Sobolev et al (1997). Another possibility might be superradiance as described by Rajabi et al (2019) pertaining to the flaring methanol masers associated with S255IR-NIRS3. It is not clear what best describes the conditions of the maser environment nor this rapid variation presented here.…”
Section: An Accretion Event?mentioning
confidence: 99%
“…We simulate the cylindrical sample of methanol molecules ( 0 = 2 × 6.7 GHz, = 0.7 D) described in over a duration = 10 8 s, having length = 2 × 10 15 cm, radius = 5.4 × 10 7 cm, population inversion relaxation time constant 1 = 1.64 × 10 7 s, and polarisation dephasing time constant 2 = 1.55 × 10 6 s. Despite such time scales being orders of magnitude longer than those typically used in maser models of star formation regions, there is in theory no physical barrier to their occurrence. In Rajabi et al (2019) it is shown that 2 = 1.55 × 10 6 s corresponds to a gas density of approximately 10 5 cm −3 . Rather than precluding such a large value of 2 on account of an assumption of high gas density, the very natural fit of the SR model in Rajabi et al (2019) under such a value of 2 may be considered evidence of low gas density in the star formation region which it models.…”
Section: Experiments Descriptionmentioning
confidence: 99%
“…The initial preparation of equation ( 16) would be realised by a pumping flare of finite duration shorter than that of the SR transient process, but of sufficient amplitude to raise the inverted population column density above the SR threshold. In Rajabi et al (2019), for example, the 6.7 GHz methanol emission is believed to be pumped by infrared radiation from dust (Sobolev et al 1997) We assume that the relevant photon wavelengths are much larger than the size of a molecule, and we neglect the Hilbert space associated with the motions of the molecules' centres of masses. We also assume that the molecules are sufficiently separated so as not to require wavefunction symmetrisation.…”
Section: Superradiance As a Transient Processmentioning
confidence: 99%
See 2 more Smart Citations